(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Burn injuries, especially severe burns, triggers immune and inflammation response, disturbances of metabolism and distributive type of shock, all of this can be said as hard to treat and may lead to cause multiple organ failure. The fact that the injury not only effects physical health but also mental health his mental health and quality of life is critical. As a result, people with burn injuries cannot be deemed recovered if wounds have healed; rather, burn injuries cause long-term fundamental changes that must be focused in order to improve quality of life. As a result, burn care providers encounter a variety of issues, including managing acute and critical care, long-term care, and rehabilitation. Hand is the most commonly injured body part out of all accidents that are work related , ranks third of all workplace injuries and necessitating surgical and lengthy recovery. Hand burns make it difficult to function. The rehabilitation process has benefited from the usage of virtual reality (VR). LMC is a form of virtual reality game that uses new technology to provide biofeedback and training for fine motor function and functional skills. According to this review paper, leap motion training will enable hand burns patient to enhance finger mobility, reduce scar thickness, and improve hand function along with enhancing quality of life of patient. Although improvement in condition depends on severity of burn but this gadget proved to be a boon for hand rehab. on burn population. . Finally in conclusion of review it can be said that leap motion training may aid patients with hand burns in increasing finger range of motion, reducing scar thickness, and improving hand function.